Investigation of the effects of kinesiophobia level on physical activity and quality of life in university students (Journal of Ideas in Health, 2023)
Background: Kinesiophobia, which is called activity avoidance, is a condition that may cause university students to stay away from physical activity more. This study aimed to understand how physical activity and quality of life levels of university students with different levels of kinesiophobia are affected. Methods: Our study included 395 students who were studying at Ankara Medipol University in the 2022-2023 academic year and were accepted to participate in our study. The kinesiophobia, physical activity, and quality of life levels of the students were evaluated with questionnaires. The Demographic Characteristics of Students were analyzed using Chi-Square and Mann-Whitney U tests. Spearman correlation analysis was used for the correlation between the scores of the scales, and Mann-Whitney U was used for comparing physical activity levels and quality of life according to kinesiophobia levels. Statistical significance was set as p0.05). In our study, while all parameters of WHOQOL and TKS were correlated with each other, only physical and psychosocial sub-parameters of WHOQOL and IPAQ were correlated (p